Cord Blood Vitamin D Status Is Associated With Cord Blood Insulin and C-Peptide in Two Cohorts of Mother-Newborn Pairs - Switkowski, Karen M (J Clin Endocrinol Metab, 2019)
CONTEXT: Vitamin D may be important for prenatal programming of insulin and glucose regulation, but maternal vitamin D deficiency during pregnancy is common. OBJECTIVE: We examined associations of early vitamin D status with markers of fetal insulin secretion: cord blood insulin and c-peptide. We hypothesized that maternal 25-hydroxyvitamin D (25(OH)D) during pregnancy and cord blood 25(OH)D would both be positively associated with cord blood insulin and c-peptide. METHODS: We studied mother-newborn pairs from two cohorts: Project Viva (n = 862 pairs included) and Genetics of Glucose Regulation in Gestation and Growth (Gen3G; n = 660 pairs included). We analyzed associations of the cord blood hormones with maternal 25(OH)D using generalized additive models with nonlinear spline terms, and with cord blood 25(OH)D using multivariable linear regression models. RESULTS: The 25(OH)D levels were <75 nmol/L in >70% of mothers and 85% of newborns. Maternal and cord blood 25(OH)D levels were correlated (Project Viva, r = 0.58; Gen3G, r = 0.37). Maternal 25(OH)D had an inverted-U–shaped relationship with cord blood insulin and c-peptide in both cohorts. Cord blood 25(OH)D had a linear relationship with the cord blood hormones. In fully adjusted models, each 10-nmol/L increase in cord blood 25(OH)D was associated with higher cord blood insulin and c-peptide concentrations: 3.7% (95% CI, 0.09 to 7.5) and 3.2% (95% CI, 0.8 to 5.6), respectively, in Project Viva; 2.2% (95% CI, −0.1 to 4.6) and 3.6% (95% CI, 1.0 to 6.3), respectively, in Gen3G. CONCLUSION: Vitamin D may play a role in regulating fetal insulin secretion, potentially affecting glucose regulation and growth.